TYPE AND DENSITY OF FISH IN THE INDRAGIRI RIVER LUBUK TERENTANG VILLAGE, GUNUNG TOAR DISTRICT, KUANTAN SINGINGI REGENCY, RIAU PROVINCE - Aqila, Nesha; Sumiarsih, Eni; Fajri, Nur El (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Indragiri River has high fishery potential. Fishing activities conducted however, affect fish population in general. A research aims to determine the community structure of fish in that waters was conducted in 16-21 August 2018. Fish was sampled every day for 15 days. The fish was captured using gill net, nets and fishing rods. Data analyzed were density fish and type of fish. There were 21 types of fish captured, they were belonged to 9 families, namely Cyprinidae, Belontidae, Osphronemidae, Siluridae, Bagridae, Loricarinae, Helostomatidae, Pangasidae and Mastecemlidae. The highest fish density is Barbodes schanefeldi (Kapiek) 46,183 and the lowest is Macrognathus pardalis (tilan) 0,015.